Implementasi Prinsip Keadilan dalam Praktek Pembagian Warisan pada Masyarakat Desa Barbaran - Chandra Ali Hanapiah Lubis; Maulida Hasnah Pulungan; Suci Rahmadani (PT. Willy Print Art, 2025)
Inheritance distribution is a legal and social issue with both normative and sociological dimensions. This study aims to analyze the implementation of the principle of justice in inheritance distribution practices in the Barbaran Village community and its compliance with Islamic law. This study used a qualitative method with an empirical approach, through in-depth interviews with religious leaders, traditional leaders, and heirs, as well as field observations. This study aimed to examine how the principle of justice is implemented in inheritance distribution practices in the Barbaran Village community. The results indicate that inheritance distribution practices in Barbaran Village are generally carried out in accordance with Islamic law, both in terms of the timing of distribution, the determination of heirs, and the proportion of inheritance distribution. The principle of justice applied is proportional, as stipulated in the Qur'an and Hadith, and is reinforced through family deliberation as a means of reaching agreement and maintaining harmony. Thus, inheritance distribution practices in the Barbaran Village community are not only normatively valid according to Islamic law but also socially and culturally relevant.